2019
DOI: 10.1002/jso.25451
|View full text |Cite
|
Sign up to set email alerts
|

Malignant bowel obstruction

Abstract: Malignant bowel obstruction (MBO) is a common problem for patients with advanced malignancy, especially colorectal and ovarian cancers. Symptoms include pain, bloating, nausea and vomiting, and inability to eat. Treatment options consist of a wide range of surgical and nonsurgical interventions (medications, endoscopic, or interventional radiology approaches). Outcomes are variable no matter the strategy, and the optimal approach is often not clear. Greater research is needed to assist decision-making for clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 34 publications
0
42
0
4
Order By: Relevance
“…The quality of life for patients with MSBO post-surgery is largely unstudied and when it has been studied, the tools used are unvalidated. 7 A 2016 Cochrane review of MSBO identified no data on quality-of-life scores. 4 The ability of patients to tolerate oral intake after surgery, time spent out of the hospital, and discharge to home have all been used as surrogate quality-of-life metrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of life for patients with MSBO post-surgery is largely unstudied and when it has been studied, the tools used are unvalidated. 7 A 2016 Cochrane review of MSBO identified no data on quality-of-life scores. 4 The ability of patients to tolerate oral intake after surgery, time spent out of the hospital, and discharge to home have all been used as surrogate quality-of-life metrics.…”
Section: Discussionmentioning
confidence: 99%
“…With multiple different therapeutic options for management of MSBO, including endoscopic, medical, surgical, and palliative care approaches, determining which patients would benefit most from surgery is critical. 7 Certain clinical factors, such as dependent functional status, older age, presence of ascites, and preoperative nutritional status are associated with poorer surgical outcomes and can therefore be used to help guide decision-making. 4 8 9 The effects of other clinical factors on surgical outcomes, such as the type of malignancy, extent of metastatic disease, and patient response to systemic treatment, are less well studied.…”
Section: Introductionmentioning
confidence: 99%
“…A su vez, en el 80 % de los pacientes con cáncer avanzado, la OGIM puede presentar múltiples niveles de obstrucción en relación con un diagnóstico previo de carcinomatosis peritoneal. Por otra parte, puede ser secundaria a su tratamiento, como sucede en la formación de fibrosis o enteritis por radiación, etiología benigna como bridas hasta en un 20 %, e indeterminada en un 12 % (6)(7)(8).…”
Section: Introductionunclassified
“…1 Although the exact definition of MBO varies, one generally accepted version constitutes clinical symptoms of bowel obstruction concomitant with evidence of primary or secondary intra-abdominal cancer. 2 MBO may occur as a result of cancer advancement (eg, tumor over-growth), anti-cancer treatment (eg, radiation scarring), or other benign factors (eg, adhesive blockade). In later stages, the obstructed intestinal segments may impede the passage of intraluminal contents, resulting in imbalance of electrolyte or even mesenteric ischemia.…”
Section: Introductionmentioning
confidence: 99%